Evaluating the trends of China's ecological civilization construction using a novel indicator system. (1st October 2016) - Zhang, Xiaohong; Wang, Yanqing; Qi, Yan; Wu, Jun; Liao, Wenjie; Shui, Wei; Zhang, Yanzong; Deng, Shihuai; Peng, Hong; Yu, Xiaoyu; Qi, Hui
Abstract: Ecological civilization construction has become one of the key strategies to address China's serious resource and environmental issues. However, how to define and how to assess ecological civilization ( EC ) are worth further exploring. This paper constructed a people-oriented EC indicator system, composed of a set of indicators, viz. Degree of Physiological Equilibrium ( DPE ), Degree of Psychological Imbalance ( DPI ), Degree of Imbalance of Human and Environment ( DIHE ), Degree of Human Development ( DHP ), Disharmony Degree of Economy and Environment ( DDEE ), and a composite index-Ecological Civilization Index (ECI), and then the indicator system was used to investigate the trends of China's EC construction during 1980–2010. Based on the reference year 1980, the study revealed that: (1) Physiological equilibrium of Chinese people has been slightly disturbed; (2) Psychological balance of Chinese people has been broken seriously; (3) The balance between human and environment has been destroyed greatly; (4) China has achieved great progress in promoting human development; (5) this country has improved the relationship between economy and environment obviously, despite that this improvement pace still falls behind speed of economic growth; and (6) China's EC level has declined during this study period. Therein, psychological problem and conflict between human and environment are the key obstacles to China's EC progress. China's government should further emphasize reform of its income distribution system and transformation of its economic development mode in the future. Highlights: Trends of China's EC construction during 1980–2010 were investigated using a novel indicator system. The declining EC level is mainly attributed to the conflict between human and environment and psychological imbalance. Reforming its income distribution system and transforming its economic development mode are urgent for this country.